The sintering and optimization of stabilised Zirconia. - Hoosain, Shaik Ebrahim. (My University, 2011)
Nano-sized 3 mol% yttria stabilised zirconia powders were synthesized from a co-precipitation technique and compared to powders obtained from Geratech Zirconium Beneficiation Ltd, a zirconium chemical plant company based in Johannesburg. The aim of this research was to investigate the possibility whether these powders could compete commercially with established international companies producing the same powder. The co-precipitated powder was then subjected to various calcination treatments. Both these powders were then characterized using XRD (including Rietveld refinement), SEM, and DTA/TGA. These powders were then milled extensively and then uniaxially compressed into cylindrical pellets at 250 MPa. These resulting pellets were then subjected to sintering in air at various temperatures for two hours. The properties of the ceramic produced from these powders were assessed and compared to the commercial Wieland Zeno disc. The microstructural features and the phase composition were examined using SEM and Rietveld Refinement. The mechanical properties such as hardness and toughness were determined using Vickers indentations. Fracture strength values were obtained using standard three point bend tests. These mechanical properties were then compared to values obtained for bio-grade zirconia ceramics. Values obtained generally consistent with most of the previously published work and the theories behind the remarkable properties in zirconia-based ceramics. Sintering conditions played a major role in the properties obtained for the ceramic as these conditions all had an effect on grain size, phase composition, and relative density and porosity. All these factors were found to have an effect on the final properties of the ceramic.